Factors Influencing Customer Satisfaction of Online Banking With Special Reference to Jaffna District - Umakanth, N.; Waidyalankara, R.W.R.N.S.B. (Faculty of Commerce and Management, Eastern University Sri Lanka, 2022)
The world is changing quickly; expansions in information technology have a massive impact on the banking industry, frequently generating additional convenient payment methods and user-friendly banking services. The environment has already understood the importance of innovation. Earlier, furthermost banking businesses were carried out through face to-face banking methods and as an outcome of operating manual banking transactions, customers and banks had to face various difficulties. Online Banking is a popular system that banks can use as a substitute. The main objective of this study is to identify the Factors Influencing Customer Satisfaction with Online Banking with Special Reference to the Jaffna district. The researcher selected state-owned and private sector banks in the Jaffna district for the study, and the data was collected through online questionnaires. Hundred and fifty (150) customers using online banking facilities in some banks were identified for the study. The Factor analysis and Multiple Regression were used to analyze the collected data. Under previous studies, the researcher selected eleven factors that influence customer satisfaction with the use of Online Banking, namely security and privacy; availability; ease of use; user-friendliness; website features; Trust; social influence and Responsiveness; relative advantages; service quality; Compatibility; and customer support services. After conducting an Exploratory Factor analysis, those eleven factors were reduced to two elements: availability and website features. The study's findings identified Relative Advantages and Compatibility significantly influence Customer Satisfaction Online. The banking industry can use the recommendations provided in the survey to improve the usage of Online Banking in the study area.
Keywords: Online Banking; Customer Satisfaction; Compatibility; Factor Analysis; Multiple regression